Prevalence and factors associated with symptoms of depression, anxiety and stress among traffic police officers in Kathmandu, Nepal: a cross-sectional survey - Pranil Man Singh Pradhan; Binita Yadav; Anil KC; Sandesh Bhusal (BMJ Open)
Objective This study aimed to assess the prevalence of depression, anxiety and stress, associated factors and stress-coping strategies among traffic police officers in Kathmandu, Nepal.Design Cross-sectional survey.Setting Kathmandu Valley, Nepal.Participants A total of 300 traffic police officers working under the different traffic units of Kathmandu Valley for at least 6 months were recruited via a simple random sampling procedure.Primary outcome measures State of depression, anxiety and stress among traffic police officers based on the Depression, Anxiety and Stress Scale.Secondary outcome measures Coping strategies under stressful conditions based on the Coping Orientation to Problems Experienced Inventory (Brief-COPE) tool.Results Altogether 124 (41.3%) traffic police officers had symptoms of depression, 141 (47%) had anxiety symptoms and 132 (44%) had symptoms of stress. Smoking was significantly associated with an increased likelihood of experiencing symptoms of depression (adjusted OR (AOR): 10.7, 95% CI: 4.8 to 23.6), anxiety (AOR: 7.1, 95% CI: 3.4 to 14.9) and stress (AOR: 6.8, 95% CI: 3.3 to 14.1). Similarly, longer working hours was significantly associated with higher odds of experiencing symptoms of depression (AOR: 3.4, 95% CI: 1.8 to 6.4), anxiety (AOR: 2.3, 95% CI: 1.3 to 3.9) and stress (AOR: 1.9, 95% CI: 1.1 to 3.4), and lack of physical exercise was associated with an increased likelihood of exhibiting depressive symptoms (AOR: 2.3, 95% CI: 1.1 to 4.7). Participants in this study used positive coping strategies more than negative coping strategies.Conclusion Our study found a high prevalence of depression, anxiety and stress symptoms among traffic police officers in Kathmandu Valley, Nepal. Smoking and longer working hours were associated with an increased likelihood of experiencing symptoms of depression, anxiety and stress, and lack of physical exercise was associated with an increased likelihood of depressive symptoms.